Surface modifications for antimicrobial effects in the healthcare setting: a critical overview. Issue 3 (July 2018) - Adlhart, C.; Verran, J.; Azevedo, N.F.; Olmez, H.; Keinänen-Toivola, M.M.; Gouveia, I.; Melo, L.F.; Crijns, F.
Summary: The spread of infections in healthcare environments is a persistent and growing problem in most countries, aggravated by the development of microbial resistance to antibiotics and disinfectants. In addition to indwelling medical devices (e.g. implants, catheters), such infections may also result from adhesion of microbes either to external solid–water interfaces such as shower caps, taps, drains, etc., or to external solid–gas interfaces such as door handles, clothes, curtains, computer keyboards, etc. The latter are the main focus of the present work, where an overview of antimicrobial coatings for such applications is presented. This review addresses well-established and novel methodologies, including chemical and physical functional modification of surfaces to reduce microbial contamination, as well as the potential risks associated with the implementation of such anticontamination measures. Different chemistry-based approaches are discussed, for instance anti-adhesive surfaces (e.g. superhydrophobic, zwitterions), contact-killing surfaces (e.g. polymer brushes, phages), and biocide-releasing surfaces (e.g. triggered release, quorum sensing-based systems). The review also assesses the impact of topographical modifications at distinct dimensions (micrometre and nanometre orders of magnitude) and the importance of applying safe-by-design criteria (e.g. toxicity, contribution for unwanted acquisition of antimicrobial resistance, long-term stability) when developing and implementing antimicrobial surfaces.